Aplikasi Multimedia Interaktif Pembelajaran Hiragana Jepang Pada Sman 13 Kabupaten Tangerang - Yuli Nadiroh; Rachmat Hidayat (Universitas Bina Sarana Informatika, 2017)
In the world of education, multimedia is used as a medium for effective learning to create interesting applications and easy to use as well as the technology improves the efficiency of environmental assessment in learning software, therefore the author makes application of Interactive Multimedia Learning Japanese Hiragana In SMAN 13 Tangerang Regency authors using Adobe Flash Professional CS5 and Photoshop 7.0 as the software needed for the manufacture of this multimedia. Multimedia is simply to learn the hiragana characters, hiragana itself to students or beginners who want to understand the Japanese language starts by learning Hiragana Japanese writing of letters used. In addition, Interactive Multimedia Applications Learning Japanese Hiragana In Tangerang regency SMAN 13 is designed such that it can interact with the wearer.Kata Kunci: Aplikasi Multimedia Interaktif, Hiragana Dan Multimedia Interaktif Pembelajaran